Factor affecting independent living of persons with intellectual disabilities: a systematic review - Mohd Zambri, Insyirah; Amin, Aizan Sofia; Mohd Kamil, Nur Khaleeda; Md Akhir, Noremy; Sutan, Rosnah; Khairuddin, Khairul Farhah; Wan Abdullah, Wan Arnidawati (Human Resource Management Academic Research Society, 2023)
Evidence indicates that the transition process to adulthood represents a critical and confusing time in the life of any person with intellectual disabilities (PWID). However, PWID often experiences adaptive functioning deficits that negatively impact an individual's ability to achieve independence. Many previous studies only focus on persons with physical disabilities and place less emphasis on the empowerment of independent living for PWID. Therefore, this systematic literature review, guided by the publication standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), tries to identify the factors that could affect PWID to live independently. This study selected articles using two databases: Scopus and Web of Sciences, from 2017 to 2020, resulting in a total of 607 articles. Overall, only 28 selected articles were discussed in this review after the quality appraisal process using Mixed Methods Appraisal Tool (MMAT). In sum, this systematic review found two main themes: individual factors and environmental factors. For individual factors, there are four sub-themes: gender, cognitive ability, self-attitudes and skills. Whereas, for environmental factors, there are eight sub-themes family, community, policy, technology, economy, health, education and geographical location. Thus, this study contributes to the conceptual framework for future research involving independent living for PWID.